Davide Domeneci & Nicoló Marchetti (eds.) Urbanized Landscapes in Early Syro-Mesopotamia and Prehispanic Mesoamerica. Papers of a Cross- Cultural Seminar held in Honor of Robert McCormick Adams. Wiesbaden, Otto Harrasowitz GmbH & Co. KG, 2018. 224. ISBN 978-3-447-11086-0, e- ISBN 978-3-447-19782-3 - Jaruf, Pablo (2018)
Fil: Jaruf, Pablo F. Universidad de Buenos Aires. Instituto Multidisciplinario de Historia y Ciencias Humanas; Argentina